2022
DOI: 10.3390/s22051694
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Analysis of Hand Gesture Recognition with Temporal Convolutional Networks

Abstract: In recent years, the successful application of Deep Learning methods to classification problems has had a huge impact in many domains. (1) Background: In biomedical engineering, the problem of gesture recognition based on electromyography is often addressed as an image classification problem using Convolutional Neural Networks. Recently, a specific class of these models called Temporal Convolutional Networks (TCNs) has been successfully applied to this task. (2) Methods: In this paper, we approach electromyogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Several recent studies have shown that CNNs can effectively extract underlying motor control information from EMG signals in both offline data sets [12]- [14] and real-time control scenarios [15]. Combining CNNs feature-extracting architectures with other network modules (e.g., Recurrent Neural Networks (RNN) [16], Long Short-Term Memory networks (LSTM) [17], [18], or Temporal Convolutional Networks (TCN) [19], [20]) has resulted in even higher offline movement decoding performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shown that CNNs can effectively extract underlying motor control information from EMG signals in both offline data sets [12]- [14] and real-time control scenarios [15]. Combining CNNs feature-extracting architectures with other network modules (e.g., Recurrent Neural Networks (RNN) [16], Long Short-Term Memory networks (LSTM) [17], [18], or Temporal Convolutional Networks (TCN) [19], [20]) has resulted in even higher offline movement decoding performance.…”
Section: Introductionmentioning
confidence: 99%
“…A CNN-SE architecture was selected because it demonstrated significant improvement over several of the state-of-the-art CNNs [22] and promising results in bio-signal classification tasks (i.e., electrocardiogram [23], [24] and electroencephalogram [25], [26]), and recently also for offline EMG gesture recognition [27], [28]. The choice of the other three networks allowed us to investigate if the promising offline results of increasing the number of hidden layers in FFNNs [8] and the reportedly high performance of TCN's [19], [20] would translate to an online control scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that CNNs can effectively extract underlying motor control information from EMG signals in both offline data sets [12]- [14] and real-time control scenarios [15]. Combining CNNs feature-extracting structures with other network modules (e.g., Recurrent Neural Networks (RNN) [16], Long Short-Term Memory networks (LSTM) [17], [18], or Temporal Convolutional Networks (TCN) [19], [20]) has resulted in even higher offline movement decoding performance.…”
Section: Introductionmentioning
confidence: 99%
“…A CNN-SE architecture was selected because it demonstrated significant improvement over several of the state-of-the-art CNNs [22] and promising results in bio-signal classification tasks (i.e., electrocardiogram [23], [24] and electroencephalogram [25], [26]), and recently also for offline EMG gesture recognition [27], [28]. The choice of the other three networks allowed us to investigate if the promising offline results of increasing the number of hidden layers in FFNNs [8] and the reportedly high performance of TCN's [19], [20] would translate to real-time control scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-EMG-based methods for gesture recognition have already been proposed by several publications, among them artificial neural networks, to achieve up to 87% accuracy with a single-channel-sensor when attempting to distinguish four different gestures [5]. Generally, black-box neural networks, particularly convolutional neural networks, have emerged in popularity to analyze sEMG gesture data [6][7][8][9][10][11][12][13][14][15][16][17]. A composition consisting of a Bayes classifier and a k-Nearest-Neighbors classifier can achieve up to 93% accuracy for four different gestures with one channel [18].…”
Section: Introductionmentioning
confidence: 99%